2016
DOI: 10.18632/oncotarget.13575
|View full text |Cite
|
Sign up to set email alerts
|

Gene and microRNA modulation upon trabectedin treatment in a human intrahepatic cholangiocarcinoma paired patient derived xenograft and cell line

Abstract: Intrahepatic cholangiocarcinoma (ICC) is an aggressive and lethal malignancy with limited therapeutic options. Trabectedin has a high antitumor activity in preclinical models of biliary tract carcinoma (BTC), being a promising alternative treatment. Here, we studied the effect of trabectedin at transcriptomic level on an ICC patient derived xenograft (PDX) and on the derived cell line, MT-CHC01. Further, putative targets of trabectedin were explored in the in vitro model. In vitro, trabectedin inhibited genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…miRNAs have been implicated in the pathogenesis of CCA 42 45 because upregulated miRNAs suggest an oncogenic role and downregulation of miRNAs may be suppressive, so dysregulated miRNAs are correlated with the adverse clinical features, diminished survival, and poor prognosis of CCA patients. 46 Selaru et al 36 proved that miR-21 was oncogenic by inhibiting PDCD4 and TIMP3 suppressor genes in the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been implicated in the pathogenesis of CCA 42 45 because upregulated miRNAs suggest an oncogenic role and downregulation of miRNAs may be suppressive, so dysregulated miRNAs are correlated with the adverse clinical features, diminished survival, and poor prognosis of CCA patients. 46 Selaru et al 36 proved that miR-21 was oncogenic by inhibiting PDCD4 and TIMP3 suppressor genes in the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, miRNA-29a/205/221 show promises serving as tissue biomarkers of chemosensitivity in CCA patients. Furthermore, trabectedin, an anti-metastatic agent in CCA has been found to inhibit metastasis via downregulating the expression of gene SYK and LGALS1 [ 76 ]. These two genes are the direct targets of certain miRNAs such as MiR-21-3p, miR-21-5p and miR-31-3p and miR-1207-5p, miR-1225-5p separately, suggesting the overexpression of these miRNAs is closely associated with the effectiveness of trabectedin [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor growth arrest was associated with an about 50% reduction of HER2 mRNA and protein expression levels, as well as with a drop in the intracellular PCho content in SKOV3.ip cells. Several studies have shown that Trab induced a down‐modulation of mitogen‐activated protein kinase and EGFR signaling in cancer cell lines and patient‐derived xenografts and AKT–mTOR signaling in EOC . Therefore, we hypothesize that the decrease of tCho and PCho following Trab treatment might indicate a down‐modulation of oncogenic signaling and therefore reduced cell proliferation …”
Section: Discussionmentioning
confidence: 93%